Application of self-monitoring and feedback procedures to improve tumble turns in swimming - Ayvazo, S.; Naveh, M.-E. (International Journal of Sport and Exercise Psychology, 2026)
Behavioural feedback procedures such as self-monitoring, verbal feedback, and goal-oriented feedback have been experimentally implemented using single-subject research methodologies and have shown promising effects on improving athletic performance in various sports. Despite the inherent challenges of providing feedback in aquatic environments, applications of behavioural feedback procedures in swimming are relatively underexplored and methodologically limited. Using an A-B-A-BC multitreatment design, this study aimed to address methodological limitations of previous single-subject studies in swimming and demonstrate enhanced experimental control. This study examined the effects of a self-monitoring and verbal feedback intervention, later augmented with goal-oriented feedback, on the complete and accurate tumble-turn performance of four competitive young swimmers aged 10-13 years. Data were collected using a direct observation event recording measurement. Social validity ratings were also collected from the swimmers. The findings indicate performance levels improved immediately and showed accelerating trends for all youth swimmers following the implementation of the self-monitoring and verbal feedback intervention, resulting in an average increase of 40.4%. When a do-your-best goal-oriented feedback component was added, performance levels were further enhanced for three of the four swimmers, approaching a ceiling effect, and showed an average increase of 36%. The results reveal a functional relation between the self-monitoring and feedback procedures and the observed improvements in complete and accurate tumble-turn execution. Furthermore, the swimmers generally perceived the intervention as valuable and beneficial. This study successfully replicated and extended Schonwetter et al.`s (2014) study by demonstrating the utility of behavioural procedures in improving the complex tumble-turn skill.